A simplified protocol for the generation of cortical brain organoids - Eigenhuis, Kristel N.; Somsen, Hedda B.; van der Kroeg, Mark; Smeenk, Hilde; Korporaal, Anne L.; Kushner, Steven A.; de Vrij, Femke M. S.; van den Berg, Debbie L. C. (Frontiers in Cellular Neuroscience, 2023)
Human brain organoid technology has the potential to generate unprecedented insight into normal and aberrant brain development. It opens up a developmental time window in which the effects of gene or environmental perturbations can be experimentally tested. However, detection sensitivity and correct interpretation of phenotypes is hampered by notable batch-to-batch variability and low reproducibility of cell and regional identities. Here we describe a detailed, simplified protocol for the robust and reproducible generation of brain organoids with cortical identity from feeder-independent induced pluripotent stem cells (iPSCs). This self-patterning approach minimizes media supplements and handling steps, resulting in cortical brain organoids that can be maintained over prolonged periods of time and that contain radial glial and intermediate progenitors, deep and upper layer neurons, and astrocytes.